Pediatric papillary thyroid carcinoma successfully managed with a multimodal approach - Pal, Rimesh; Dayal, Devi; Menon, Prema; Muthuvel, Balasubramaniyan; Devarapalli, Soumya; Mishra, Purbasha (International Journal of Research in Medical Sciences, 2017)
Malignant tumours of the thyroid gland are rare in children. The tumours tend to be advanced at the time of presentation, but the overall survival is still better as compared to adults. The use of radioiodine ablation or treatment for the post-thyroidectomy gland remnants or recurrences improves patient survival. The reports of a multimodal approach that involves surgery as the primary treatment along with radioiodine ablation (RIA) are rare in the pediatric age group. We describe here a child with metastatic papillary thyroid carcinoma treated with a multimodal approach.